Propuesta de un plan estratégico de marketing para el centro de desarrollo infantil “Kids” de la ciudad de Loja - Vaca Tumbaco, Darwin Renán (2017)
The present itesis work this guided to the proposal of a strategic plan of marketing for the Center of Infantile Development Kids of the loja city that allows to guide the managerial management of the organization toward the innovation of products and services educatvos to satisfy the necessities of the users to create demand and to locate new markets potentials starting from a program of publicity and marketing for the means of more covering to go into in the local and provincial market. For that which strategies, political, tactical, goals were determined, activities, responsible and the respective budget for the execution of each one of the strategic objectives so that the entity takes possession in the market. The investigative work was carried out to give execution to a prerequisite to opt Engineer's grade in Administration of Companies. The fieldwork was made by means of the observation, interviews and surveys to the Directress of the Center and the whole personal administratvio and educational in a number of 9; and, to the family parents like external clients in a number of 41, instruments that served as sources of gathering of valid information. The strategic plan begins with the organizational analysis of the educational center, obtaining a result pondered in the evaluation of factors internal strengths - weaknesses where its ponderaciones and qualifications are based on the study and analysis that show the internal position in which is the entity investigated as for their activities and necessary operations; it shows a pondered result of 2,38 the same one that this below the average of 2,5; mostrandio an organization with internal weaknesses that should be overcome short term, by means of a management acertiva of the directive. This doesn't mean that the center of infantile development KIDS of the city of Loja has internal strengths that will be considered to eliminate the existent weaknesses and this way to take advantage of the competitive environment to improve its products and services and to expand in the local and provincial market; to capture new clients, to recover lost clients and to improve the institutional image. The product of the situational external analysis; it represents a pondered quantitative result of 2,76 points what indicates that the educational company takes advantage of the existent opportunities in its environment and it minimizes the negative possible effects of the external threats. Among the most outstanding conclusions we have that the institution doesn't have mission, vision neither corporate values settled down rightfully exposed in visible places; but if they are applied tacitly; this omission doesn't allow him/her to show its corporate image and to grow in followers; a recommendation would be that the educational Company locates new markets potentials starting from a program of publicity and marketing for the means of more covering to go into in the local and provincial market. 56% of those interviewed to the internal of the entity manifests that they work with a collective vision, in front of 44% that not this sure of the vision that you/they have. Finishing same way that the entity needs to decree in official form which is exactly the vision of the educational center and to give it to know stops in combined form to achieve the objectives and proposed goals. We also observe that the total (100%) of those interviewed affirms that the Center doesn't carry out any type of publicity. This actions gave the rule of the one in route to continuing in the elaboration of a marketing plan to develop the administrative management of the infantile center. The implementation of the strategic plan of marketing for educational entity will have a total budget of $ 11.662,50 that will be financed with own resources.